Dual‐responsive shape memory hydrogels with self‐healing and dual‐responsive swelling behaviors. Issue 13 (27th November 2020) - Yang, Qianyu; Gao, Chen; Zhang, Xuemei; Zhao, Xingyu; Fu, Yiqing; Tsou, Chihui; Zeng, Chunyan; Yuan, Li; Pu, Zejun; Xia, Yiqing; Sheng, Yuping; Fang, Yu
Abstract: Shape memory hydrogels (SMHs) can fix the hydrogels in a provisional shape and restore the initial shape under external stimulation. Herein, a dual‐responsive shape memory hydrogel with dual‐responsive swelling and self‐healing properties is presented in this work. The SMHs were fabricated by one‐step emulsion copolymerization of acrylic acid (AAc), acrylamide (AAm) and stearyl methacrylate (SMA). Sodium alginate (SA) was introduced as an interpenetrating polymer in the network. With ionic cross‐linking between ‐COO − and Fe 3+ or saline‐reinforced hydrophobic association, the hydrogels can be fixed in a provisional shape, which can be restored by immersing the hydrogels in vitamin C solution or pure water, respectively. When the as‐prepared hydrogels were immersed in FeCl3 solutions, additional ionic cross‐linking between Fe 3+ and ‐COO − could be formed, thus constructing the dual physically cross‐linked (DPC) network, which endows the hydrogels with excellent fracture stress (2.6 MPa) and toughness (5.47 MJ/m 3 ). Besides, the reversible physical cross‐linkings endowed the hydrogel with outstanding self‐healing capability. Furthermore, the pH and saline responsive swelling properties of the SMHs are additional fantastic properties. Therefore, we believe that this simple strategy provides a great opportunity for the preparation of SMHs with multiple intellectual performances. Abstract :